2022
DOI: 10.1002/cnr2.1694
|View full text |Cite
|
Sign up to set email alerts
|

The role of MiRNA‐433 in malignant tumors of digestive tract as tumor suppressor

Abstract: Background MicroRNAs (miRNAs) are a class of short non‐coding RNAs with a length of approximate 22 nuclei acids that can be expressed both as an oncogene and tumor suppressor gene in human cancers. MiRNAs can participate in the post‐ transcriptional regulation of gene expression, and regulate the several cancer‐related processes, including proliferation, apoptosis, metastasis, etc. Recent findings Expression of miRNA‐433 has been reported to vary in different tumors and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…MMP3 is regulated by various miRNAs [18,19], subsequently facilitating tumor cell invasion and metastasis [15][16][17]. The abnormal expression of miRNAs has been closely associated with processes such as tumor cell invasion and metastasis in osteosarcoma [18,19,[52][53][54]. For example, the increased expression of MMP-3 induces tumor metastasis in osteosarcoma by inhibiting miR-519d [19], and miR-134 reduces osteosarcoma cell invasion and metastasis by targeting MMP-3 in vivo and in vitro [18].…”
Section: Discussionmentioning
confidence: 99%
“…MMP3 is regulated by various miRNAs [18,19], subsequently facilitating tumor cell invasion and metastasis [15][16][17]. The abnormal expression of miRNAs has been closely associated with processes such as tumor cell invasion and metastasis in osteosarcoma [18,19,[52][53][54]. For example, the increased expression of MMP-3 induces tumor metastasis in osteosarcoma by inhibiting miR-519d [19], and miR-134 reduces osteosarcoma cell invasion and metastasis by targeting MMP-3 in vivo and in vitro [18].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that overexpression of miR-433-5p prevents motor impairment and inflammation by targeting MAPK1 [ 180 ]. Moreover, miR-433-5p has been reported to suppress cancer cell proliferation and metastasis by modulating tumor signaling pathways or target genes [ 181 ]. Lower levels of hepatic PIK3CD in type 2 diabetes have been associated with decreased insulin sensitivity induced by miR-125b [ 182 ].…”
Section: Proven and Potential Study Of Novel Cernets In Pcosmentioning
confidence: 99%
“…As per the research done in 2020 by Jinhui Xue et al, the existence speed of the high-expression group was much higher than that of the low-expression group. This result raised the possibility that miRNA-433 could be a marker for the malignancy of mammary cancer [ 36 ]. Shiqin Liu et al initially argued that miRNA-433 could decrease tumor growth in ER+ BC by preventing M2 macrophage polarisation.…”
Section: Tumor Suppressor Mirnas In Bcmentioning
confidence: 99%